Are greener start-ups of superior quality? The impact of environmental orientation on innovativeness, growth orientation, and international orientation - Thomas Neumann (Journal of Innovation and Entrepreneurship, 2023)
This paper merges the literature on green and high-quality entrepreneurship by introducing environmental orientation as an unrecognised characteristic of start-up quality and the three quality dimensions innovativeness, growth orientation, and international orientation. Entrepreneurship literature argues that only high-quality start-ups contribute to sustainable development and that a better understanding of what determines the quality of start-ups is required. Empirical research has recently shown that the environmental orientation of start-ups is one such determinant, as it significantly predicts their innovativeness. This paper pursues this novel research avenue on the importance of environmental orientation for start-up quality in two ways. First, this paper evaluates and extends this initial evidence on environmental orientation and innovativeness by examining a three times larger sample, covering additional countries and entrepreneurial stages. Second, this paper also analyses the impact of environmental orientation on the quality dimensions of growth orientation and international orientation. Investigation using Global Entrepreneurship Monitor data on 9650 entrepreneurs from 51 countries revealed that start-ups with a higher environmental orientation are of superior quality regarding their innovativeness, growth expectations, and exports. These results remain robust for start-ups at different entrepreneurial stages, and tests employing different methodological approaches and variable definitions. However, the categorisation into factor-driven, efficiency-driven, and innovation-driven countries showed that greener start-ups are more innovative in countries at all three levels of development, while the relationships with growth orientation and international orientation remained significant for only two of the three categories. The findings of this paper provide a new approach for practitioners to identify the small number of high-quality start-ups and an economic reason warranting intensified efforts to support green start-ups.
Keywords: 650; Innovation; Entrepreneurship; Developing countries; Environmental orientation; International; Nascent entrepreneurship; Startup